Análisis jurídico al incremento de las indemnizaciones por despido intempestivo, contemplados en el código laboral vigente, propuesta de reforma de ley. - León Vásquez, Juan Elías (2014)
The importance of this thesis is that the constitutional rights of individuals with regard to the right to work are not being implemented in a socially appropriate manner. This is a reality, not only accepted the theoretical, conceptual and doctrinal part, but it is proven in real life, where, according to the contact and the opinions given by the same lawyers stated that unemployment is a reality latent where sectors are the most affected due to lack of opportunities provided by both public institutions and by private companies related to employment.